Investigating the thermoelectric power generation performance of ZnCuO: A p-type mixed-metal oxide system. (April 2022) - Ali, Hafiz T.; Amami, Mongi; Rehman, U.; Mahmood, K.; Yusuf, Mohammad; Ikram, Salma; Ali, A.; Amin, N.; Javaid, K.; Imran Arshad, M.
Abstract: Thermoelectric power generation performance of ZnCuO nanostructures is enhanced by varying the concentration of Cu atoms. This is tested by growing samples of ZnCuO by simple hydrothermal route at different Cu concentrations (x = 0, 0.1, 0.2, 0.3, 0.4 and 0.5). The X-ray diffraction (XRD) pattern shows the formation of mixed-metal oxide phases of ZnO and CuO, while the increase in Cu concentration results in generation of more stable CuO phases. Raman spectroscopy measurement is performed for all synthesized samples, which supports the XRD results. For the thermoelectric and electric conductivity behavior, Seebeck coefficient and Hall measurements are performed for all samples. Data suggest an improvement in Seebeck coefficient from 32 to 73 μV°C −1 with the increase of Cu concentration in the host crystal. Electrical conductivity data also show a similar increasing trend (19–36 Scm −1 ) resulting in a high power-factor value of 1.12 × 10 −5 Wm −1 K −2 for the sample with highest Cu concentration. This enhanced thermoelectric performance with increasing concentration of Cu atoms is due to the improvement of carrier mobility. The mobility of carriers is thought to increase because of the emergence of mixed composite phases, as verified by XRD and Raman spectroscopy measurements. Highlights: Synthesis of Cu-doped ZnO samples at different copper doping concentrations. Modulation of copper doping resulted in formation of mixed-metal oxide phases. Seebeck coefficient and electrical conductivity was found to be increased due to increase in carrier mobility with the formation of mixed phases. Power-factor value was increased up to 1.12 × 10 −5 Wm −1 K −2 .